RASER-FISH: non-denaturing fluorescence in situ hybridization for preservation of three-dimensional interphase chromatin structure - Brown, J; De Ornellas, S; Parisi, E; Schermelleh, L; Buckle, V (Springer Nature, 2022)
DNA fluorescence in situ hybridization (FISH) has been a central technique in advancing our understanding of how chromatin is organized within the nucleus. With the increasing resolution offered by super-resolution microscopy, the optimal maintenance of chromatin structure within the nucleus is essential for accuracy in measurements and interpretation of data. However, standard 3D-FISH requires potentially destructive heat denaturation in the presence of chaotropic agents such as formamide to allow access to the DNA strands for labeled FISH probes. To avoid the need to heat-denature, we developed Resolution After Single-strand Exonuclease Resection (RASER)-FISH, which uses exonuclease digestion to generate single-stranded target DNA for efficient probe binding over a 2 d process. Furthermore, RASER-FISH is easily combined with immunostaining of nuclear proteins or the detection of RNAs. Here, we provide detailed procedures for RASER-FISH in mammalian cultured cells to detect single loci, chromatin tracks and topologically associating domains with conventional and super-resolution 3D structured illumination microscopy. Moreover, we provide a validation and characterization of our method, demonstrating excellent preservation of chromatin structure and nuclear integrity, together with improved hybridization efficiency, compared with classic 3D-FISH protocols.